2021
DOI: 10.3390/genes12091328
|View full text |Cite
|
Sign up to set email alerts
|

MED12 Mutation in Two Families with X-Linked Ohdo Syndrome

Abstract: X-linked intellectual deficiency (XLID) is a widely heterogeneous group of genetic disorders that involves more than 100 genes. The mediator of RNA polymerase II subunit 12 (MED12) is involved in the regulation of the majority of RNA polymerase II-dependent genes and has been shown to cause several forms of XLID, including Opitz-Kaveggia syndrome also known as FG syndrome (MIM #305450), Lujan-Fryns syndrome (MIM #309520) and the X-linked Ohdo syndrome (MIM #300895). Here, we report on two first cousins with X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
3
3
0
Order By: Relevance
“…Based on the study in 77 causative MED12 variants, Plassche and Brouwer (2021) declared that the three clinically named syndromes, FGS1, LS, and XLOS, were attributed to only eight out of 77 variants, which means a high heterogeneity of phenotype of MED12 deficiency. This conclusion was supported by our and previously reported four cases ( Caro-Llopis et al, 2016 ; Martínez et al, 2017 ; Rocchetti et al, 2021 ) due to MED12 R296Q. Rocchetti et al (2021 ) compared the phenotypes in the four patients with R296Q, who shared only microcephaly/brachycephaly and micrognathia/microretrognathia out of 24 identified craniofacial signs, and the only phenotype, broad thumbs and halluces, of extremities was found in one of the patients.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Based on the study in 77 causative MED12 variants, Plassche and Brouwer (2021) declared that the three clinically named syndromes, FGS1, LS, and XLOS, were attributed to only eight out of 77 variants, which means a high heterogeneity of phenotype of MED12 deficiency. This conclusion was supported by our and previously reported four cases ( Caro-Llopis et al, 2016 ; Martínez et al, 2017 ; Rocchetti et al, 2021 ) due to MED12 R296Q. Rocchetti et al (2021 ) compared the phenotypes in the four patients with R296Q, who shared only microcephaly/brachycephaly and micrognathia/microretrognathia out of 24 identified craniofacial signs, and the only phenotype, broad thumbs and halluces, of extremities was found in one of the patients.…”
Section: Discussionsupporting
confidence: 75%
“…This conclusion was supported by our and previously reported four cases ( Caro-Llopis et al, 2016 ; Martínez et al, 2017 ; Rocchetti et al, 2021 ) due to MED12 R296Q. Rocchetti et al (2021 ) compared the phenotypes in the four patients with R296Q, who shared only microcephaly/brachycephaly and micrognathia/microretrognathia out of 24 identified craniofacial signs, and the only phenotype, broad thumbs and halluces, of extremities was found in one of the patients. In comparison with previously reported cases due to MED12 R296Q ( Caro-Llopis et al, 2016 ; Martínez et al, 2017 ; Rocchetti et al, 2021 ) and clinical features summarized by Plassche and Brouwer (2021) , the pattern of fetal clenched hand with overlapping fingers and clubfoot is reported for the first time in our study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The gene encodes the mediator of the RNA polymerase II transcription subunit 12 protein, a member of the mediator complex (MED), with a length of 2178 amino acids [ 5 ]. This protein acts as a gene-expression regulator in all eukaryotes and plays a role in developmental signaling pathways [ 6 ]. Baskin et al [ 5 ] demonstrated that MED12 directly stimulated the transcriptional activity of myocyte enhancer factor 2 and that it was required for the maintenance of cardiac function by regulating calcium-handling genes through interactions with myocyte enhancer factor 2.…”
Section: Introductionmentioning
confidence: 99%